Economic growth and income distribution in the development of China's dual economy - Wang, Dihai, 1972- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Since the start of the process of economic reform in 1978, China has maintained the structure of a dual economy, with concurrent development of the agricultural and industrial sectors. This book explores the key issues of China's economic growth and income distribution in this context. Pivoting on analysis of China's real GDP and growth rate, the first part of the book analyzes the evolution of economic growth and characteristics of economic structural changes across a period of forty years, scrutinizing the different determinants that contribute to growth. Then, chapters in the second part of the volume study the relationship between China's economic growth and economic development, elucidating the mechanism of interaction between the former and key factors of the latter, including investment, housing, education, and healthcare. The final chapters center on the development and current landscape of income distribution, providing explanation for sharpening income inequalities and advancing suggestions and feasible solutions to the problem of income gap. This book is targeted at scholars, students and policymakers interested in China's economy, income distribution, and economic growth"--
Keywords: Dual economy -- China; China -- Economic conditions -- 1976-2000.; China -- Economic conditions -- 2000-; BUSINESS & ECONOMICS / Development / General; BUSINESS & ECONOMICS / Development / Economic Development